Die Stadt, das Geld und der Markt. Immobilienspekulation in der Bundesrepublik 1960-1985 - Führer, Karl Christian (Studien zur Zeitgeschichte, 2016)
In West Germany profit-hungry speculators were blamed for rising real estate prices and rental costs. Karl Christian Führer analyzes events in the real estate markets in major cities such as Frankfurt, Munich, Hamburg, Cologne, and West Berlin and the heated debate about speculation before 1985. He shatters popular notions while offering salient new data for an informed discussion about freedom and regulation in the housing market.